The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1139/x02-192
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication végétative de l'Acer saccharum: contribution à la micropropagation

Abstract: Pour la première fois, toutes les étapes de la micropropagation de l'érable à sucre (Acer saccharum Marsh.) ont été complétées avec succès. Les bourgeons de plus de 200 plants d'érable à sucre âgés de 2 ans ont été débarrassés de leurs écailles et mis en culture sur un milieu contenant les sels de Murashige et Skoog ainsi que les éléments organiques de Bourgin et Nitsch, tous dilués au tiers, avec ou sans régulateur de croissance. Le taux de survie des explants en fin d'induction a été supérieur sur un milieu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Although TDZ has been shown to increase shoot production, many other reports have demonstrated that TDZ does not benefit or hinders shoot production and elongation (Yusnita et al 1990;Lu 1993;Kartsonas and Papafotiou 2007). In contrast, TDZ either alone or in combination with other plant growth regulators was successfully used for in vitro propagation of Acer and Fraxinus species (Kim et al 1997;Brassard et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Although TDZ has been shown to increase shoot production, many other reports have demonstrated that TDZ does not benefit or hinders shoot production and elongation (Yusnita et al 1990;Lu 1993;Kartsonas and Papafotiou 2007). In contrast, TDZ either alone or in combination with other plant growth regulators was successfully used for in vitro propagation of Acer and Fraxinus species (Kim et al 1997;Brassard et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The development of axillary nodes from explants was also performed on MS medium containing 4.90 M IBA and 13.31 M of BA [22]. Citric acid has been recognized as a very efficient anti-oxidant compound in in vitro culture [23,24]. It prevents the production of polyphenols which often hinder organogenesis and cause explant necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, thidiazuron (TDZ) was used singly or combined with other PGRs to successfully micropropagate the hard maple, sugar maple (Brassard et al, 2003). In this study, we placed explants on DKW media containing TDZ at 0.001, 0.01, and 0.1 μM.…”
Section: Methodsmentioning
confidence: 99%
“…Micropropagation of field-grown woody plants can be difficult because of contamination and exudates from cut woody stems (Brassard et al, 2003;Kerns and Meyer, 1986;Padilla and Encina, 2004;Preece, 1991). Foliar pubescence of bigtooth maple makes tissue culture sterilization potentially difficult because surface disinfestation solutions may not fully coat the abaxial leaf epidermis (Barker, 1974).…”
Section: Introductionmentioning
confidence: 99%